2011
DOI: 10.1111/j.1525-1594.2011.01205.x
|View full text |Cite
|
Sign up to set email alerts
|

Electrocardiogram‐Synchronized Rotational Speed Change Mode in Rotary Pumps Could Improve Pulsatility

Abstract: Continuous-flow left ventricular assist devices (LVADs) have greatly improved the prognosis of patients with end-stage heart failure, even if continuous flow is different from physiological flow in that it has less pulsatility. A novel pump controller of continuous-flow LVADs has been developed, which can change its rotational speed (RS) in synchronization with the native cardiac cycle, and we speculated that pulsatile mode, which increases RS just in the systolic phase, can create more pulsatility than the cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
59
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 58 publications
(62 citation statements)
references
References 30 publications
2
59
0
1
Order By: Relevance
“…The tVAD simulation was intended as a baseline experiment that represents the use of tVADs in clinical application today. There are numerous studies that have investigated augmented pulsatility in tVADs through speed modulation [1,3,4,16,26,27,33,34]. These studies have shown improved levels of pulsatility, left ventricular unloading and blood flow through the aortic valve, but were exceeded by the values of our pVAD simulation.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…The tVAD simulation was intended as a baseline experiment that represents the use of tVADs in clinical application today. There are numerous studies that have investigated augmented pulsatility in tVADs through speed modulation [1,3,4,16,26,27,33,34]. These studies have shown improved levels of pulsatility, left ventricular unloading and blood flow through the aortic valve, but were exceeded by the values of our pVAD simulation.…”
Section: Discussionmentioning
confidence: 92%
“…Previous studies have investigated synchronization ratios (1:2 and 1:4) lower than the HR under one given phase-shift setting [24] with the intention of establishing a weaning protocol. The importance of considering the pump timing and systolic fraction as an integral part of the investigation has been shown in vivo by [2] for pVADs and by [1,3,4,26,33,34] both in silico and in vivo for tVADs.…”
Section: Discussionmentioning
confidence: 99%
“…We have already reported details of our novel pump controller, which can change the RS of the EVAHEARTÒ so it is synchronized with the cardiac cycle [7,8,12,13]. We defined the systolic phase as 33% of the RR interval and the diastolic phase as 67% of the RR interval, and input the duration of each phase in accordance with the heart rate.…”
Section: Study Protocol and Lvad Controlmentioning
confidence: 99%
“…With this unit we define the distance and rotational speed (RS) of the systolic and diastolic phases to drive the EVAHEARTÒ so it is synchronized with the native heart rate. By using normal heart goat models [7] we have already shown that we can change the coronary flow (CoF) [8] by use of its remarkable pulsatility. In the work discussed in this report we wished to determine whether it was possible to change the native heart load by use of this system, by investigating the LV end-diastolic volume (EDV) with normal and acute heartfailure models.…”
Section: Introductionmentioning
confidence: 99%
“…Such a pulsatile driving technique had not been tried or discussed before our group's recent report. [30][31][32][33][34][35][36] Using this system in normal goats' hearts, we found that coronary flow (CoF) could be altered according to the control mode. 30, 31 If we can achieve strong CoF by controlling the rotation of the cf-LVAD, in synchrony with the cardiac beat, we may have a atients with severe heart failure (HF) are treated with a multidisciplinary approach of medical management, including left ventricular assist device (LVAD) 1,2 and heart transplantation, and the prognosis has tremendously improved these days.…”
mentioning
confidence: 99%